1970
DOI: 10.1111/j.1095-8649.1970.tb03250.x
|View full text |Cite
|
Sign up to set email alerts
|

River flow and upstream movement and catch of migratory salmonids

Abstract: Six years' data from the River Coquet together with published information for other British rivers show that upstream migrant salmon and sea trout tend to be intercepted at counting fences and be caught on rod and line when river flows are somewhat higher than average and not when they are at their extreme values, though there is no particular river flow favoured all the year round. In years of highest river discharge the number of fish entering the River Coquet and the number of fish caught on rod and line ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 1 publication
1
51
0
1
Order By: Relevance
“…However, about half of the guides also thought that trout were easily caught on a rising river or during steady flows. The opinions of local guides are similar those of Alabaster (1970) who found that salmon migrate up stream in response to a freshet and that more salmon were caught at flows slightly above normal. As flow in the Tongariro River is controlled artificially this river provides an opportunity to examine the effect of flow and barometric pressure on trout migration and so to verify the soundness of the anglers views.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, about half of the guides also thought that trout were easily caught on a rising river or during steady flows. The opinions of local guides are similar those of Alabaster (1970) who found that salmon migrate up stream in response to a freshet and that more salmon were caught at flows slightly above normal. As flow in the Tongariro River is controlled artificially this river provides an opportunity to examine the effect of flow and barometric pressure on trout migration and so to verify the soundness of the anglers views.…”
Section: Introductionsupporting
confidence: 68%
“…Brown & Mackay (1995) also found less pre-spawning movement in cutthroat trout during periods when flows were higher than average than during periods of stable flow. Alabaster (1970) found that Atlantic salmon and sea trout tended to move into traps on above average flow, although the average flow at which fish were trapped was not constant seasonally or from year to year.…”
Section: Individual Fish Movementsmentioning
confidence: 95%
See 1 more Smart Citation
“…(b) A number of authors (Lamond, 1916 ;Huntsman, 1939 ;Stuart, 1957 ;Stewart, 1969 ;Alabaster, 1970;Hellawell et al ., 1974) have suggested a rather more complex model in which S. salar and S. trutta move only on certain parts of the hydrograph, usually the rising and falling limbs, rather than the spate peak . The work by Stewart on Lancashire rivers was developed further by Cragg-Hine (1985) .…”
Section: River Flowmentioning
confidence: 99%
“…River Coquet ( Fig. 2) The 90-km river is relatively unmodified and important to anglers because of its migratory sea trout and salmon (Alabaster, 1970); diverse organizations have helped to ensure that a high river quality is maintained. The whole river (and some adjacent woodland) was designated a Site of Special Scientific Interest in 1996.…”
Section: Sample Sitesmentioning
confidence: 99%